EVALUASI USER EXPERIENCE DENGAN PENDEKATAN USABILITY TESTING PADA SISTEM INFORMASI SMART ACADEMIC - Ria Andriani (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2020)
ABSTRACTSmart Academic is an information system used by administrative staff to manage administrative activities from upstream to downstream related to academia starting from the pre-lecture process such as Her-Registration of new students, filling in Study Plan Cards, and class division during the lecture process such as semester exams as well as the assessment process of each course, then proceed with administrative processing for the graduation until the graduation process, so that Smart Academic becomes a critical information system for the University if a failure occurs, it will hamper the lecture process which means the system cannot fulfill its objectives. This study evaluates the Smart Academic Information System through user experience with 8 respondents using the Usability Testing approach. This study examines user experience based on the Nielsen Heuristic method, namely Visibility of System, Match Between System and The Real World, User Control and Freedom, Consistency and standards, Preventive error system, Recognition Rather Than Recall, Flexibility and Efficiency, Aesthetic and Minimalist Design, Help User Recognize dialogue, and recovers from error, and Help and Documentation. Studies prove that of the 10 Nielsen Heuristic variables, 4 variables have poor Usability values, namely the Consistency and standards variable, Preventive error system, Aesthetic and Minimalist Design, and Help and DocumentationKeywords: information system evaluation, nielsen heuristic, usability testingABSTRAKSmart Academic merupakan sistem informasi yang digunakan oleh staf administrasi untuk mengelola aktifitas administratif dari hulu ke hilir yang berhubungan dengan akademik mulai dari proses sebelum perkuliahan seperti Her-Registrasi mahasiswa baru, pengisian Kartu Rencana Studi, dan pembagian kelas, selanjutnya saat proses perkuliahan seperti ujian semester serta proses penilaian masing-masing mata kuliah, kemudian dilanjutkan dengan pengolahan administrasi untuk yudisium sampai dengan proses wisuda, sehingga Smart Academic ini menjadi sistem informasi yang kritis bagi pihak Universitas apabila terjadi kegagalan maka akan menghambat proses perkuliahan yang artinya sistem ini tidak dapat memenuhi tujuannya. Penelitian ini melakukan evaluasi terhadap Sistem Informasi Smart Academic melalui pengalaman pengguna dengan jumlah responden sebanyak 8 orang dengan menggunakan pendekatan Usability Testing. Penelitian ini mengkaji pengalaman pengguna berdasarkan metode Nielsen Heuristic yaitu Visibility Of System , Match Between System And The Real World, User Control And Freedom, Consistency and standards, Preventive error system, Recognition Rather Than Recall, Flexibility and Efficient, Aesthetic and Minimalist Design, Help User Recognize dialogue, and recovers from error, dan Help and Documentation. Studi membuktikan bahwa dari 10 variabel Nielsen Heuristic terdapat 4 variabel yang memiliki nilai Usability kurang baik yaitu pada variabel Consistency and standards, Preventive error system, Aesthetic and Minimalist Design, dan Help and Documentation.Kata Kunci: evaluasi sistem informasi, nielsen heuristic, usability testing